REFORMULASI TAFSIR AL-QUR’AN DI ERA MODERN (Telaah Historis Dinamika, dan Transformasi Metodologi Interpretasi) - Wely Dozan; Farihin; Lalu Masaji (al-Afkar, Journal For Islamic Studies, 2022)
Epistemology of the study of the methodology of interpretation is a necessity in the civilization of the Islamic world, because the current interpretation has experienced dynamics and paradigms, especially in the methodology, model, and application of interpretation. This has become one of academic anxiety, especially for the author to examine further its relation to the methodology of interpretation in the modern era. The focus of this research is trying to photograph how the development of modern interpretation, then how the methodology, model, and application of the interpretation of the Qur'an. Of course this is the basic assumption in this study. The type of this research is library research or known as literature research with a descriptive analysis approach by looking for problems and answering related issues that are studied through books, articles, journals, and relevant references. Keywords, the methodology of interpreting the Qur'an in the classical to modern-contemporary eras have shown very rapid dynamics, especially in terms of methodology and nuances of interpretation orientation. Interpretation of the Qur'an in the modern era is trying to ground and restore the spirit of the Qur'an with the birth of the Qur'an as an analytical knife, as if the Qur'an still exists and is able to respond to various problems of the people. So that the product or characteristic of the interpretation of the modern era is being able to place the Qur'an as (shalihun likulli era wa makkan). Therefore, understanding or interpreting the Qur'an does not stop textually, however, the mainstream of modern era interpretation, namely the nuances of its interpretation, is contextual. This is the reformulation or typical methodology of the interpretation of the Qur'an in the modern era.